The technical importance of ceramic glass in the production of contemporary works of art - کمال, : ڕۆژگار کمال محمد (Sulaimani Journal for Humanities, 2025)
The title of this paper is (The technical importance of ceramic glass in the production of contemporary works of art) and the technical and aesthetic characteristics of glass in new ceramic art. This research consists of four parts. The first part consists of the general framework of the research. The purpose of the research is to familiarize us with the importance of ceramic glass technique in the production of contemporary art works, then identify the scope of research on ceramic glass technique in contemporary art between 1995-2020, which was a turning point. The second part consists of two papers, the first paper on contemporary ceramic art and the second paper on the technical and aesthetic characteristics of ceramics and the glazing process, and previously conducted research close to this topic, and then show some examples used by the researcher. The third part is devoted to the research procedures, including the researcher relied on the descriptive method for this research, the research community includes (6) ceramic works, the research sample consists of three contemporary ceramic works identified by the researcher and analyzed the samples. Finally, Section 4 contains the results, the most important of which are: * In ceramic products, full attention has been paid to color, glass and working techniques In light of the results and discussion, the most important conclusions are as follows: * The role of techniques in ceramic work and their adaptation to the glass of the product. At the end of the study, recommendations and suggestions about this study This is followed by sources and a summary in Arabic.